WAYS TO INCREASE THE COMPETITIVENESS OF AN ENTERPRISE (Academicia Globe: Inderscience Research, 2024)
In the ever-evolving landscape of business, enterprises are constantly challenged to enhance their competitiveness to thrive amidst fierce competition. This abstract outlines key strategies for increasing enterprise competitiveness. These strategies encompass innovation and adaptability, customer-centric approaches, strategic partnerships, talent development, operational excellence, market differentiation and branding, and strategic use of data and analytics. By adopting a holistic approach that integrates these strategies, enterprises can strengthen their competitive edge, respond effectively to market dynamics, and achieve sustainable growth. This article explores how enterprises can implement these strategies to navigate challenges, seize opportunities, and emerge as leaders in their respective industries.